From burden to backbone: the regenerative potential of food waste through digital, biological, and technological innovation - Girotto, Francesca; Beggio, Giovanni (Frontiers in Nutrition, 2025)
This perspective article outlines a cross-sectoral roadmap that leverages digital, biological, and material innovations to transform unavoidable food and beverage organic waste into high-value resources. In this manuscript, the term “regenerative circular bioeconomy” refers to a systemic approach that not only minimises waste and closes resource loops but also enhances the resilience of natural and social systems. “Upcycling” is here defined as the transformation of organic residues into products of higher functional or economic value compared to their original use. “Digital enablers” are considered as data-driven tools, such as artificial intelligence, machine learning, and digital twins, which support the optimisation and monitoring of valorisation processes. Artificial intelligence is positioned as a systemic enabler of real-time diagnostics, redistribution, and forecasting, supporting both the quantification and reduction of organic waste. In parallel, the integration of mathematical modelling with digital technologies is increasingly driving the development of data-driven algorithms aimed at optimising process conditions for upcycling strategies within valorisation pathways. Regarding traditional recovery routes, the article highlights frontier technologies including microbial electrochemical systems, solar photoreforming, and green extraction methods. It also presents cutting-edge applications such as the use of organic waste in biocomposites and the emerging biomedical upcycling of slaughterhouse by-products for tissue engineering. Through this interdisciplinary lens, the article advocates for a regenerative circular bioeconomy supported by infrastructural investment, ethical governance, and comprehensive life-cycle validation.